Analysis of Corporate Governance Based on The Agency Theory - I. Wikartika; Fajar Syaiful Akbar (Future Science)
Improved company performance can support the company's survival to continue to survive in the future. The corporate governance system provides effective protection for shareholders and creditors so they are sure they will get a return on their investment correctly. Corporate governance also helps create a conducive environment for the creation of efficient and sustainable growth in the corporate sector. The implementation of corporate governance in Indonesia has not been able to meet expectations so that it has become one of the causes of economic instability that has an impact on the decline in corporate financial performance. The enforcement of good corporate governance is also used to minimize conflicts of interest between shareholders and company management or agency problems. This study aimed to determine the effect of corporate governance on corporate financial performance. Corporate governance was proxied by using institutional ownership and concentration of ownership, while the company's financial performance was proxied by using Tobin's Q. The research method used was a quantitative method using multiple linear regression analysis techniques. The study population used companies listed on LQ45 on the Indonesia Stock Exchange. The research sample of 45 companies in 2018. The results showed that institutional ownership did not affect dividends and financial performance. The concentration of ownership affected the dividends and dividends affected the financial performance, but the concentration of ownership did not affect the financial performance of the company.